Women in Sallust: a prosopographic and historiographical study - Posadas, Juan Luis (Gerión. Revista de Historia Antigua, 2012)
The historian must study all the women mentioned in an ancient author to make a statement or a judgement about him. Only working in that way, we can understand the role of women in the Sallustian history: the roman women are denigrated as immodest and adulteress, the foreigner are praised as brave and virtuous. Despite the fact of this, we can conclude that Sallust is a good author in order to study the actuation of some women in the final years of the Roman republic, just if we ignore some aspects of his narration.